Revisions of the Afrotropical genera of Argidae and species of Pampsilota Konow, 1899 (Hymenoptera, Tenthredinoidea) - Andrew D. Liston; Georg Goergen; Frank Koch (Deutsche Entomologische Zeitschrift, 2017)
The Afrotropical fauna contains five genera of Argidae. These are keyed. New subjective synonyms, followed by the valid name in brackets, are Calarge Enslin, 1911 [Arge Schrank, 1802], Calarge africana Enslin, 1911 [Arge congrua Konow, 1907], Clyparge Pasteels, 1963 [Scobina Lepeletier & Serville, 1828], Clyparge terminalis Pasteels, 1963 [Scobina poecila (Klug, 1834)], and Sterictophora [sic] afra Pasteels, 1963 [Sphacophilus afer comb. n., species inquirenda near S. monjarasi Smith & Morales-Reyes, 2015]. The type material of both C. terminalis and S. afra was probably collected in the New World, but labelled with the wrong locality “Kamerun”. An introduction of both species to Africa, not followed by long-term establishment, seems less likely. The removal of these taxa from the faunal list of the region is recommended. The nine known Afrotropical species of Pampsilota are revised, and an illustrated dichotomous identification key presented, with distribution maps for all species. Four species are here described as new to science: P. dahomeyanus Goergen, Koch & Liston, sp. n., P. nigeriae Liston & Koch, sp. n., P. tsavoensis Liston & Koch, sp. n., and P. zebra Liston & Koch, sp. n. Lectotypes are designated for Pampsilota afer Konow, 1899, and Cipdele africana Mocsáry, 1909. The immature stages and host plant of only one species are known: P. dahomeyanus on Lannea nigritana (Anacardiaceae). Its larval morphology strongly resembles that of European and North American species of Arge. We provisionally retain Pampsilota as a valid genus, although it could justifiably be treated as comprising merely a species group, or groups, within Arge.